George Grant and the theology of the cross : the Christian foundations of his thought - Athanasiadis, Harris (University of Toronto Press, 2001)
Beneath the philosophical, social, political, ethical, national, and moral issues that Grant tackled throughout his career was a fundamental concern with theodicy - the problem of faith in God in a world of conflict, suffering, and tragedy.